2020
DOI: 10.2174/1874285802014010065
|View full text |Cite
|
Sign up to set email alerts
|

The Role of IL-6, TNF-α, and VDR in Inhibiting the Growth of Salmonella Typhi: in vivo Study

Abstract: Background and aim: The prevalence of typhoid fever is reportedly high, especially in Asia. When a pathogen enters the human body, there are markers in the form of molecules that will be known by the innate immune system. Specific molecular markers of gram negative bacteria, which are Lipopolysaccharides (LPS) and Toll-Like receptors-4 will interact with LPS. The binding between LPS and TLR-4 will give rise to activation signals that will activate innate immune cells. Immune cells will rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
2
11
0
1
Order By: Relevance
“…Previous study revealed that other host susceptibility gene such as Vitamin D Receptor (VDR) could inhibit the growth of Salmonella typhi in vivo. [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study revealed that other host susceptibility gene such as Vitamin D Receptor (VDR) could inhibit the growth of Salmonella typhi in vivo. [37].…”
Section: Discussionmentioning
confidence: 99%
“…Several study related with immune response in typhoid fever like the role of IL6, TNF alpha in inhibit of S. typhi in vitro dan In some cases salmonella typhi infection may affect TLR4 expression in vivo [12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Following S. Typhi infection, signalling pathways within cells trigger the release of cytokines (Keuter et al, 1994). Importantly, IL-6 is an essential multifunctional cytokine that exerts its proinflammatory and anti-inflammatory properties (Febriza et al, 2020). This cytokine derives from different cells of the human body, such as endothelial cells, lymphocytes, macrophages, astrocytes and ischemic myocytes; thus, it can regulate many pathological and physiological activities (Niculet et al, 2021).…”
Section: Ciprofloxacin Could Alter Cytokines Levels In Patients With ...mentioning
confidence: 99%
“…The host immune system recognises the causative agent Salmonella via recognition receptors, importantly Toll-like receptors (TLR) (Kurtz et al, 2017). This could promote downstream signalling pathways and activate an inflammatory response by releasing cytokines such as TNF-a, IL-1, IL-6 and IL-8 (Andrade and Andrade Júnior, 2003;Febriza et al, 2020). These crucial mediators including cytokines play a key role in attracting phagocytosis cells like macrophages, polymorphonuclear neutrophils (PMNs) and monocytes, which are involved in bacterial inhibition (Febriza et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have examined the use and effects of traditional medicines for various diseases [ [1] , [2] , [3] , [4] , [5] ], including the effects of herbal medicines on infectious diseases, such as candidiasis [ [6] , [7] , [8] ], typhoid fever [ [9] , [10] , [11] , [12] , [13] , [14] ], toxoplasmosis [ [15] , [16] , [17] ], gingivitis [ 18 , 19 ], vaginitis [ 20 ], and the human immunodeficiency virus (HIV) [ 21 , 22 ], and noninfectious diseases such as diabetes [ 23 ].…”
Section: Introductionmentioning
confidence: 99%